Financial Statement Fraud: Challenges and Technology Deployment in Fraud Detection - Othman, Intan Waheedah (International Journal of Accounting and Financial Reporting, 2021)
Fraudulent financial reporting and other forms of earnings misstatement are catastrophic and pose a considerable threat to capital market stability. This study reviews the literature on existing technology-based methods of detecting financial statement fraud. The aim is to describe the challenges of predicting a rare fraud event and provide an understanding of the various data-mining based techniques for financial statement fraud detection. Given that fraudsters are becoming more adaptable and are constantly devising new ways to outwit the fraud detection system, the study provides directions for future research in detecting the evolutionary fraudulent financial reporting.